Relacionamentos interorganizacionais como fonte de vantagem competitiva: um estudo em empresas do APL de calçados da grande João Pessoa-PB - Oliveira, Iris Stéfani Viana de (2014)
This work aims to investigate how interorganizational relationships between constituent companies of the Great Joao Pessoa s shoes APL may contribute to the development of relational rents and competitive advantage. Thus, first, a literature review using the Resource Based View and as the main theoretical bases, especially Relational View and Extended Resource Based View was held. Thus, through the concepts of the literature investigated, it was possible to develop an analytical model consists of three major steps: characterization of the inter-relationships of the APL companies, identification of interorganizational resources and identifying potential sources of relational rents and competitive advantage. This research is characterized by a multi-case study by analyzing three companies of the Great Joao Pessoa s shoes APL. Moreover, it has predominantly qualitative and descriptive. Especially semi-structured interviews with managers of different companies investigated were used to collect data. For organization and analysis of qualitative data, the Atlas/ti software was used. It was found as the main common characteristics interorganizational relationship of the three companies: trust; sharing of tangible and/or intangible resources; joint learning; different degrees of collaboration; cooperation; interdependence between formally established partnerships; informal partnerships, in the figure of its managers and employees; and interaction with public and/or private institutions. Main interorganizational resource raw materials, parts, equipment, space, knowledge and information about aspects or not the production process that are shared between the companies were identified; use of the road network, proximity to ports, low cost of labor-intensive interaction with the region and private institutions of autonomous services; besides the tax incentives granted by the state government especially. As sources of relational rents knowledge sharing routines, complementary resource endowments and the existence of governance mechanisms were identified. Accordingly, therefore, there is the presence of potential for the generation of relational rents, indicating that relationships between companies in the Great João Pessoa s shoes APL may bring, varying according to the level of partnership, competitive advantages for companies forming part of them.